Impact of fiscal policies and green financing on firm innovation and firm value for green economic recovery - Long Tengfei; Ahsaan Ullah (Heliyon, 2024)
The worldwide spread of the COVID-19 epidemic has led to a rise in the costs of natural resources, which has increased production prices, slowed productivity, and threatened financial development. To stimulate the growth of sustainable economies, fiscal and monetary strategies must adopt a prioritized approach towards fostering innovation and development. The study investigates into recovery strategies by examining the influence of minute taxation reductions on power and exploring the incentives and mechanisms that drive innovation. We can estimate and deduce several outcomes by employing a variance-variance method to analyze quarterly data from Chinese companies listed in the market between Q1 2019 and Q2 2021. Enhancing energy efficiency through tax incentives can immensely benefit a company's innovative endeavors, as innovation serves to recover and expand market share. Furthermore, our research suggests that tax credits promoting energy efficiency can alleviate financial barriers and foster increased investment in innovation. Lastly, by endorsing artistic ventures, businesses can reduce costs and bolster internal cash flow. The implications of these findings are insignificant, as they propose that ineffective eco-design fiscal policies may serve as a negligible component of a limited business transformation plan for the post-COVID-19 era.